Measuring the consumption value of higher education - Annette Alstadsæter (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper argues that the consumption value of education is an important motivation for the educational choice. While controlling for ability, we document that individuals are willing to forego substantial future wage returns in order to acquire a particular type of higher education. We document that the individuals who attended Teachers' College in Norway during the 1960's had an ex ante willingness to pay for the consumption value of this educational type of at least 34% of the present value of expected potential lifetime income. The ex post price for this consumption value turned out to be 39% of their potential lifetime income.
Keywords: J24; J31; J33; I21; H89; 330; educational choice; type of education; non-pecuniary return; willingness to pay; consumption value of education; Studium; Bildungsverhalten; Nutzen; Willingness to pay; Norwegen